INCIDENCE OF ADULT POPULATION OF WORKING-AGE OF THE KRASNOYARSK TERRITORY ACCORDING TO APPEALABILITY BEHIND A MEDICAL CARE - Ольга Юрьевна Кутумова; Анатолий Иванович Бабенко; Евгений Анатольевич Бабенко (Медицина в Кузбассе, 2019)
Research objective – establishing a significance of disease classes defining appealibility of adult population of working-age behind a medical care.